Perbandingan Metode Optimasi Particle Swarm Optimization Dan Simulated Anneiling Dalam Penentuan Letak Turbin Angin Optimal - Alfiyah Shaldzabila Yustin; Lady Valent Kandioh; Herminarto Nugroho (JURNAL TEKNOLOGIA, 2020)
At present, the need for electrical energy is increasing as technology develops. The majority of the electlricity generation process uses fossil base materials with little stock left. To deal with problems of electricity needs and the lesser raw materials for the generation of electricity derived from fossils, renewable energy sources are used, one of which is wind energy. This wind power plant is usually called an wind turbine using the help of wind speed that blows to rotate the generator turbine. The amount of wind speed that passes through the turbine will greatly affect the electricity produced by the power plant. The arrangement of laying a wind turbine on a wind turbine field must be considered in order to produce more and more efficient electricity. To find out the most optimal position of turbine savings, an optimization method is used so that the wind speed of the wind turbine can be maximized even though previously the wind has passed other turbines. In this paper a Particle Swarm and Simulated Anneiling simulation method will be conducted. The data to be obtained are optimal distance between turbines and efficiency comparison between the two optimization methods in producing the optimal solution to the problem of placing wind turbines on wind turbine fields.